ARTIFICIAL INTELLIGENCE IN BANKING - Eshboyev , Temur; Eshboyeva , Madina (Effective scientific journals, 2025)
The banking industry is undergoing a major transformation as artificial intelligence (AI) technologies become increasingly embedded in processes, decision-making, risk management, and customer-facing services. This article explores how AI is being leveraged by banks and financial institutions, identifies key use-cases (such as fraud detection, credit scoring, robo-advisory, customer service), discusses the enabling technologies and organisational enablers (data and infrastructure, analytics capability, regulatory/governance aspects), reflects on the benefits (efficiency, accuracy, cost-reduction, customer experience) as well as the risks and challenges (data privacy, model bias, regulatory compliance, organisational change). Finally, the article offers a forward-looking perspective on how banks can become “AI-first” institutions, and what this means for stakeholders in banking including regulators, customers, and executives.